(untitled) (Journal of actual problems of jurisprudence, 2024)
The articleconsiders the interaction of the police and civil society institutions in the issues of ensuring the rights of men and citizens in the Republic of Kazakhstan.The existing approaches and mechanisms of interaction are analyzed, as well as the problems and prospects for the development of this area are determined.The article focuses on the importance of the participation of civil organizations in monitoring the legality of law enforcement actions, as well as the need to improve legal regulation in this area.Particular attention is paid to the practical aspects of the interaction of police and civilian organizations, including assistance to law enforcement agencies in their work and the organization of interaction within specific projects and activities.Because of the article, conclusions are drawn about the need to constantly improve the interaction of the police and civil organizations in the interest of ensuring the rights and freedoms of citizens in Kazakhstan. Keywords. Civil society, law enforcement agencies, public organizations, ensuring rights, preventing offenses, partnership, police service model.